KUALITAS PRODUK, HARGA DAN LOKASI SKINCARE MS GLOW DALAM MENENTUKAN KEPUTUSAN PEMBELIAN MELALUI MINAT BELI SEBAGAI VARIABELINTERVENING DI MS GLOW BY NOVELA.ID KABUPATEN SITUBONDO - Rahmah, Yasyfi Aufa; Karnadi, Karnadi; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Ms Glow is a local cosmetic brand that was established in 2013. The name Ms Glow itself is taken from the company’s motto, vision, and mission, namely Magic For Skin. Ms Glow products are halal certified and Ms Glow has won the Indonesia Best Brand Award (IBBA) in 2020. Ms Glow skincare products are the most complete skincare products according to the skin care needs desired by consumers. So, the focus of this study is on consumers. The population in this study is the Situbondo Regency Community. The sampling technique was determined by simple random sampling. Data analysis and hypothesis testing in this study used the Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application show that Product Quality has a significant positive effect on Purchase Interest, Price has a negative but insignificant effect on Purchase Interest, Location has a significant positive effect on Purchase Interest, Product Quality has a significant positive effect on Purchase Decision, Price has a significant positive effect on Purchase Decision, Location has a positive but insignificant effect on Purchase Decision, Purchase Interest has a significant positive effect on Purchase Decision, Product Quality has a significant positive effect on Purchase Decision through Purchase Interest, Price has a significant positive effect but insignificant effect on Purchase Decision through Purchase Interest, Location has a significant positive effect on Purchase Decision through Purchase Interest.